Urgensi Nilai-Nilai Bisnis Syariah Pada Program Dana Bergulir APBD D.I Yogyakarta - Yayan Fauzi (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
The Revolving Fund of D.I Yogyakarta Budget is the one distributed to the Yogyakarta government to the Cooperative or BMT to stimulate the development and strengthening of BMT capital (Baitul Maal Wattamwil) in the Yogyakarta area through the office of cooperatives and MSMEs. This is in accordance with Regulation of the Minister of Finance no. 218 / PMK.05 /2009 that revolving fund is funds allocated by the Ministry of State / institutions / task force of public service agencies for the strengthening of business capital for cooperatives, micro, small, medium enterprises, and other businesses under the guidance of the Ministry of State / institutions. BMT (Baitul Maal Wattamwil) or also known as Cooperatives Save Borrowing and Sharia Financing (KSPPS) is one of the businesses of Sharia financial institutions whose operational prinip based on sharia, namely the Quran and Al-Hadith. In sharia business it is important to carry out sharia values that contain 5 (five) values, namely Ownership Value, Justice Value, Balance Value, Freedom Value and Diversity Value, so that sharia financial institutions do not deviate from sharia values themselves. While the development of sharia business, which from year to year is increasing, the more BMT or KSPPS get financing programs from the government, one of which is the revolving fund program of D.I Yogyakarta Budget. Starting from 2008 who get a revolving fund program only 1 BMT out of a total of 18 cooperatives but in the revolving fund program in 2016 and 2017 there are 22 BMT out of a total of 31 and 39 cooperatives that get revolving funds apbd D.I Yogyakarta, this shows the performance and growth of BMT is good. With good performance and growth by BMT there are some BMT / KSPPS who still doubt the validity of the revolving fund program APBD D.I Yogyakarta, so it is necessary to look at the values in this revolving fund sharia. By looking at the description above, in this journal will be discussed how the Urgency of Sharia Business Values in the Revolving Fund Program APBD D.I Yogyakarta.